Ethical Decision-Making in Education: A Comparative Study of Teachers and Artificial Intelligence in Ethical Dilemmas - Karakus, Neslihan; Gedik, Kerim; Kazazoglu, Semin (MDPI, 2025)
The use of artificial intelligence (AI) in education supports long-term educational goals. AI enables learners to engage with ethical issues through simulations and virtual environments, allowing them to experience responsible decision-making in practice. Additionally, it assists administrators and educators in making data-driven decisions, contributing to the more effective formulation of educational policies. This study examines how teachers and AI address ethical educational dilemmas, comparing their decisions based on gender, experience, and education level. A total of 141 public school teachers in Turkey participated in the study, and their responses were compared with AI-generated decisions using Yin's nested multiple-case design. The scenarios were analyzed within the framework of five ethical perspectives: virtue ethics, deontological ethics, utilitarianism, social justice ethics, and situation ethics. AI aligned with teachers in five out of eight ethical dilemmas but differed in three cases, adopting a more analytical and outcome-oriented approach. In contrast, teachers placed greater emphasis on empathy and adherence to ethical principles. These findings highlight the differences in ethical decision-making between AI and teachers, emphasizing the role of AI in fostering ethical responsibility and awareness in education.
Keywords: decision-making; artificial intelligence (AI); ethical dilemmas; teacher of ethics; teacher education; Psychology